(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
In order to find out the managerial effectiveness of the managers in both public and private sector banks of West Bengal, demographic variables (age, gender, education, experience, income and marital status) and managerial effectiveness of managers are used in this study. The purpose of the present study is to find out the role of demographic variables in managerial effectiveness of managers in both public and private sector banks of West Bengal. The sample consists of 566 managers from three public (State Bank of India, Allahabad Bank, and United Bank of India) and three private (ICICI, HDFC, and AXIS) sector banks of West Bengal, out of which 487 are public bank managers and 79 are private bank managers working at various positions of management. The stratified random sampling is used for collection of data. The standard structure questionnaire named “Managerial Effectiveness Scale” was developed by Prof. S. Gupta (1996) was administered. Mean, SD, t-test and ANOVA were used to test the seven hypotheses formulated in the study. The study concludes that the mean scores of the managerial effectiveness of public and private sector bank managers are statistically significant. It also exhibits that the private bank managers are more effective than the public bank managers. The result reveals that the managerial effectiveness of both public and private sector banks managers are different with respect to some demographic characteristics like gender and experience, and age (partially). But managerial effectiveness is independent of other demographic characteristics like education, income and marital status.